Using pneumococcal and rotavirus surveillance in vaccine decision-making: A series of case studies in Bangladesh, Armenia and the Gambia. Issue 32 (6th August 2018) - ,; Wijesinghe, Pushpa Ranjan; Sargsyan, Shushan; Asoyan, Ara; Gevorya, Zaruhi; Kocharyan, Karine; Vanyan, Artavazd; Khactatryan, Sergey; Daniels, Danni; Zaman, Syed M.A.; Antoni, Sebastien; Hasan, Alvira Z.; et al.
Highlights: Pneumococcal and rotavirus surveillance are used for vaccine introduction decisions. Local institutions are key in making surveillance data available to policymakers. Existing surveillance infrastructure can be leveraged to monitor other diseases. Documenting use of surveillance should be used as advocacy to improve investments. Countries should focus efforts on building national capacity for surveillance. Abstract: Pneumonia and diarrhea are the leading causes of child morbidity and mortality globally and are vaccine preventable. The WHO-coordinated Global Rotavirus and Invasive Bacterial Vaccine-Preventable Disease Surveillance Networks support surveillance systems across WHO regions to provide burden of disease data for countries to make evidence-based decisions about introducing vaccines and to demonstrate the impact of vaccines on disease burden. These surveillance networks help fill the gaps in data in low and middle-income countries where disease burden and risk are high but support to sustain surveillance activities and generate data is low. Through a series of country case studies, this paper reviews the successful use of surveillance data for disease caused by pneumococcus and rotavirus in informing national vaccine policy in Bangladesh, Armenia and The Gambia. The case studies delve into ways in which countries are leveraging and building capacity in existing surveillance infrastructure to monitor other diseases of concern in the country. Local institutions have been identified to play a critical role in making surveillance data available to policymakers. We recommend that countries review local or regional surveillance data in making vaccine policy decisions. Documenting use of surveillance activities can be used as advocacy tools to convince governments and external funders to invest in surveillance and make it a priority immunization activity.